Finite Element Simulation of Deep Drawing Parameters Effects on Cup Wall Thickness - HASSAN, ABDUL KAREEM FLAIH; ABDULHADI, ALI HASOON (Basrah Journal for Engineering Sciences, 2014)
The present research aims to predict the thickness distribution of a wall of a deep drawn cup. A simplified 3D axisymmetric model which represents the deep drawing set (blank and tools) was created using a CAD software, and then imported into a finite element code ANSYS where a simulation was carried out. The model represents a cylindrical cup made of low carbon steel sheet. The results showed that the FE model represents real deep drawing process fairly well. The cup thickness distribution values showed a good agreement with the referenced values, where the failure or success of drawing process could be predicted based on the obtained thickness results. It was observed that a high value of friction restrains material movement and resulted in producing more thinning and more punch force. High blank holder force was found to decrease the thickness of both the bottom face of the cup and the flange rim. While increasing die corner radius increases thickness and the maximum thinning occurred at the smallest die corner radius. It was found by decreasing the punch profile radius the thickness at the flat bottom of the cup and under the punch profile region were reduced.